Hubungan Dukungan Sosial dengan Self Esteem pada Pasien Tb Paru di Puskesmas Pekauman Kota Banjarmasin - Ardianto Priwijaya; Angga Irawan; Onieqie Ayu Dhea Manto (NAJ Nursing Applied Journal, 2025)
Pulmonary tuberculosis causes physical and psychological impacts, if there is no good coping mechanism and social support, it can cause self-esteem to be disturbed. The purpose of this study was to determine the relationship between social support and self-esteem in pulmonary TB patients at the Pekauman Health Center, Banjarmasin City. The type of research is descriptive correlation with a cross-sectional design on 36 samples of pulmonary TB patients at the Pekauman Health Center, Banjarmasin City with a total sampling technique. This study used primary data obtained from questionnaires. Data analysis used univariate and bivariate Chi Square. The study found that respondents' social support was low 38.9%, moderate social support 30.6% and high social support 30.6% while low self-esteem was 50%, moderate self-esteem 27.8% and high self-esteem 22.2%. Chi square analysis obtained a p-value of 0.000 (<0.05), meaning that there was a relationship between social support and self-esteem in pulmonary TB patients at the Pekauman Health Center, Banjarmasin City.